Produção e aplicação de lacases do fungo Trametes villosa para o tratamento de efluentes - Silva, Maire Oliveira da (2024)
Water effluents have a significant environmental impact due to their ineffectiveness in treating emerging contaminants since most micropollutants and recalcitrant chemicals are not eliminated in conventional treatment plants. This work aimed to evaluate the treatment of hospital and textile effluents by applying a crude enzymatic extract containing laccase. The crude extract was produced by Trametes villosa, which showed a laccase activity of 11754 U/L. The hospital effluent samples showed a considerable reduction of 70% for caffeine, 97% for pyrazinamide, 74% for rifampicin, 66% for sulfamethoxazole, and 64% for trimethoprim. Phenolic compounds showed an average removal of 64% in hospital effluents and 98% in textile effluents. The chemical oxygen demand showed an unexpected increase in the hospital samples and a minimal reduction in the textile effluent samples. The analysis of color removal from the textile effluent showed a spectral area reduction of 3.79% for the sample treated with 500 U/L laccase and a spectral area reduction of 18.03% for samples treated with 1000 U/L laccase. The metals analyzed showed no significant reduction with enzymatic treatment. In the phytotoxicity test with Lactuca sativa, a reduction in the toxicity of some samples was observed after enzymatic treatment. The results conclude that laccase maintained its enzymatic activity after treating the samples, thus demonstrating its resistance to complex mixtures of pollutants.